Model Experiment of Construction Process of Long-Span Concrete Arch Bridge Rigid Skeleton. (October 2019) - Zhang, Shuangyang; Zhao, Ren-da
Abstract: High-speed railway passenger dedicated line have high demands for track smoothness, beipanjiang bridge as shanghai-kunming high-speed railway control project, mainspan 445m, constructed by using rigid skeleton, C80 high-strength concrete filled steel tube structure for the first time used in railway bridge; rigid skeleton in the process of construction has the traits: long span, long construction period, multi-step, mechanical behavior was extremely complex. In this paper, the design principle and similarity relation of rigid skeleton model are introduced, simplified the model construction process, and the finite element simulation analysis model is established, compared with measured values, it is shown that model test can well simulate the long span rigid skeleton arch bridge stress state in the construction process; the original construction steps have more safety reserves than simplified; the indicators of model test are within the scope of design, the results can provide technical support for the bridge construction.